Women Corrections Executives: The Keys to Reaching the Top - Collica-Cox, Kimberly (Lexington Books, 2023)
Within corrections, women have made notable impacts in policy, cultural changes, and leadership, yet they have received little attention and study. Based on quantitative and qualitative data, this book fills that gap, examining women in corrections executive positions—their motivations, successes, and challenges. From initial entry into corrections work through their careers, interviews with members of the Association of Women Executives in Corrections (AWEC) reveal their motives for promoting, their career trajectories, and the challenges they faced in a male dominated environment, such as gender bias, perceptions of leadership effectiveness, and difficulty maintaining work-life balance.